The PORTRAYAL OF PATRIARCHY IN MALALA YOUSAFZAI'A I AM MALALA - Harjani, Emilia Tetty; Saraswati, Sri (Conscientia - Journal on Language, Literature, and Culture, 2024)
The study explored the portrayal of patriarchy and the actions taken by the main character, Malala, against it in the literary work. The objectives were to reveal the depiction of patriarchy and to analyse Malala Yousafzai's responses to it in I Am Malala. The study used library research to collect the data and descriptive qualitative analytical method to analyse the data. They were analysed based on Sylvia Walby's theory on patriarchy to see the portrayal of patriarchy and liberal feminism to reveal Malala’s responses to the patriarchy. The portrayal of patriarchy in the book is seen through the experiences of the female characters, especially: Malala’s mother, Malala, Seema, Khalida, Shahida, Shabana, and Moniba. The study identified four out of six forms of patriarchy: patriarchal household production, patriarchal state, male violence, and patriarchal cultural institutions. Meanwhile, patriarchal relations in paid work and sexuality are not found. Additionally, Malala's responses to patriarchy were examined to understand female resistance; they were seen through her participation in various campaigns advocating for girls' education and acts of rebellion against patriarchy. Keywords: patriarchy, radical feminism, responses